#### Answer

$+\sqrt 2, -\sqrt2, +\sqrt 3i, -\sqrt3i$

#### Work Step by Step

$x^4+x^2-6=0$
$(x^2+3)(x^2-2)=0$
Either $x^2+3=0$ giving $x = +\sqrt 3i, -\sqrt3i$
or $x^2-2=0$ giving $x = +\sqrt 2, -\sqrt2$

Chegg costs money, GradeSaver solutions are free!

Published by
Cengage Learning

ISBN 10:
9781337271172

ISBN 13:
978-1-33727-117-2

$+\sqrt 2, -\sqrt2, +\sqrt 3i, -\sqrt3i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.